PENGARUH KEPUASAN KERJA, KEPEMIMPINAN TRANSFORMASIONAL, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SD SAINT JOHN’S MERUYA [THE EFFECT OF JOB SATISFACTION, TRANSFORMATIONAL LEADERSHIP, AND WORK MOTIVATION ON TEACHERS’ PERFORMANCE AT SAINT JOHN’S PRIMARY SCHOOL MERUYA] - Rahael Widyaningsih (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
The aim of this study was to investigate the positive effect of job satisfaction and transformational leadership to work motivation and job satisfaction, transformational leadership, and work motivation on teachers’ performance. Research was conducted at Saint John’s Primary School Meruya, West Jakarta, involving the whole 36 teachers as respondents. The method used is quantitative research. Analysis technique used is descriptive statistical analysis using path analysis tool. A structured questionnaire with Likert-type scale was used to collect data from the respondents. Data proccessed with Partial Least Squares – Structural Equation Modeling (PLS-SEM). Path coefficient shows that job satisfaction and transformational leadership have positive effect to job motivation. This study also shows that job satisfaction, transformational leadership and work motivation have positive effect to teachers’ performance.